1976
DOI: 10.1128/mmbr.40.2.403-468.1976
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of purines and pyrimidines by microorganisms.

Abstract: 435 436 437 438 438 439 439 440 440 441 441 442 444 445 446 447 447 447 448 448 448 449 449 449 449 BACTERIOL. RHv.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
192
2
3

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(203 citation statements)
references
References 231 publications
(415 reference statements)
5
192
2
3
Order By: Relevance
“…Since uric acid is introduced into the puddles from above, whether directly in feces or indirectly in oxygen-rich rain washing desiccated excreta from the rocks, aerobic uric acid decomposition will take place. Anaerobic decomposition, too, will take place, and also result in the formation of ammonia (Vogels and van der Drift 1976). I found that the aerobes capable of decomposing uric acid were more numerous than the anaerobes (Lindeboom 1979).…”
Section: Nitrogen Transformation In Thementioning
confidence: 98%
“…Since uric acid is introduced into the puddles from above, whether directly in feces or indirectly in oxygen-rich rain washing desiccated excreta from the rocks, aerobic uric acid decomposition will take place. Anaerobic decomposition, too, will take place, and also result in the formation of ammonia (Vogels and van der Drift 1976). I found that the aerobes capable of decomposing uric acid were more numerous than the anaerobes (Lindeboom 1979).…”
Section: Nitrogen Transformation In Thementioning
confidence: 98%
“…Subsequently, de novo and salvage pathways for purine biosynthesis are important components in the metabolism of all organisms. The ability to degrade purine compounds, either aerobically or anaerobically, has been identified in all kingdoms [19]. The aerobic degradation of purines is dependent on the oxidation of hypoxanthine and xanthine to uric acid via xanthine dehydrogenase ⁄ oxidase (E.C.…”
Section: The Function Of Tlp In Purine Metabolismmentioning
confidence: 99%
“…Interestingly, annotation of the DNA sequences flanking the Jannaschia sp. CCS1 HYD Js revealed an ORF encoding a putative allantoate amidohydrolase, which is part of the urate catabolic pathway in many organisms [8]. In fact, by genome data mining, another hydantoinase (HYD) was also found in the Jannaschia sp.…”
Section: Discussionmentioning
confidence: 99%